PREPARATION AND CHARACTERIZATION OF TI-PILLARED CLAYS USING TI ALKOXIDES. INFLUENCE OF THE SYNTHESIS PARAMETERS - Valverde J.L.; Sánchez P.; Dorado F.; Asencio I.; Romero A. (My University, 2003)
Titanium was introduced into the clay structure by cation exchange with polymeric Ti cations which were formed by partial hydrolysis of Ti alkoxide in HCl. X-ray diffraction, N2 adsorption-desorption, chemical analysis, thermogravimetric analysis, differential thermal analysis, temperature-programmed desorption of ammonia and temperature-programmed reduction were used to characterize the resulting Ti-pillared clays (Ti-PILCs). Titanium methoxide allows the synthesis of a solid with a large basal spacing (26 Å), a large surface area (360 m2/g), a significant amount of micropore surface area (90%), and notable acidity. Moreover, Ti-PILCs obtained from methoxide were found to be thermally stable up to 500°C. A correlation between the increase in acidity and the increases in both microporosity and Ti content was observed. The surface area, the micropore volume, the acidity and the d001 peak intensity all increased upon increasing the amount of Ti added to the preparation (up to ~15 mmoles of Ti/g clay). The use of an aqueous suspension of 0.13 wt.% of clay yielded the best structural and textural properties in terms of subsequent use of the clay as a catalyst.